Nurse in a team : cross-sectional studyof nurses' opinions on physician-nurse relationship - Sule, Zdenka (Array, 2020)
Background: For a long time, physicians have considered themselves superior to nurses, whose duty has been to carry out physicians’ orders regardless of their professional and scientific background and efficiency. Nowadays, a more professional approach to nursing profession emphasizes their professional autonomy. There are not many studies of the physician-nurse relationship that lead nurses to obedience towards physicians and their demands. We investigated nurses reactions to situations in which they are asked to fulfil physicians’ demands even when such actions are against their knowledge, beliefs or experience. Methods: We included 94 nurses, employees of the University Hospital Centre Split, Croatia in a questionnaire survey. The questionnaire included demographic data, attitudes toward their work, self-esteem scale and 3 case vignettes in which participants submitted their answers on visual analogue scales. The first case vignette was related to the nurses’ knowledge, the second one to their experience, and the third one to their professional beliefs. Results: Nurses with a high level of self-esteem were more likely to disagree with a subordinate physician-nurse relationship. Also, when it comes to their own opinion and potential, nurses were willing to carry out the demands of the physicians even when it is contrary to their knowledge, experience and beliefs. Conclusion: Even though they are aware of their autonomy and their prerogative to make their own decisions and act based on their professional competences, nurses seem to be prone to yielding to physicians’ demands in order to be accepted by their associates and to avoid any possible conflicts, even when such demands are not scientifically justified.